The Modeling Of Flood Inundation Distribution And The Institutional Index, Based On Hexahelix Collaboration, In The Downstream Of Tuntang Watershed - Ignatius Sriyana; Melfina Roselyn; Dyah Ari Wulandari (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Flooding in the Tuntang Watershed of Central Java, Indonesia, poses a significant threat to communities and infrastructure. Past mitigation strategy have been ineffective due to fragmented collaboration, limited community involvement, and insufficient policy support. This study explores a new approach that combines the Village Watershed Model (VWM) and the hexahelix collaboration framework to promote coordinated action among government, communities, academia, businesses, NGOs, and media. This research create hydrological and hydraulic modeling, analyzing stakeholder roles, collaboration levels, and flood risks using questionnaires as a method. Results indicated moderate overall collaboration, with government and community leading the efforts. The hexahelix framework proved valuable for identifying strengths, weaknesses, and opportunities for improvement. Recommendations include strengthening coordination, enhancing community participation, fostering multi-stakeholder partnerships, developing comprehensive policies and funding mechanisms, and continuing research and innovation.